(untitled) (مجلة أبحاث قانونية, 2023)
Abstract In law, the general rule is that compensation must be proportionate to the amount of damage. However, maritime law establishes, as an exception to this rule, the principle of limitation of liability due to the nature and circumstances of maritime transport. The legal limitation of the liability of the maritime carrier refers to the maximum limit the law prescribes for the compensation that this carrier must pay to the other party. This principle aims to preserve the idea of the distribution of maritime transport risks, entails special rules and mechanisms for determining the amount of compensation, and requires that, to benefit from the legal determination of the compensation, the carrier acts in good faith when performing his obligations. The legal limitation of the liability of the maritime carrier is a form of exemption from liability justified by the circumstances under which the carrier performs his obligations and that he is prevented from including contractual conditions exempting him from liability. The adoption of the principle of the limitation of liability encourages investing capital in the maritime field, thus enabling the state to build a strong commercial and economic fleet. The Libyan legislature has adopted this principle as per Article (214) of the Maritime Law. We believe that it is necessary to accede to international conventions governing maritime relations in general, and maritime transport in particular. In this study, we will approach the subject of legal determination of maritime carrier liability from an analytical and comparative perspective and will focus on three points: the principle of determining the maritime carrier liability, how to determine this liability, and the loss of the right to determine liability.